The burden of comorbidity in people with chronic kidney disease stage 3: a cohort study. Issue 1 (December 2015) - Fraser, Simon; Roderick, Paul; May, Carl; McIntyre, Natasha; McIntyre, Christopher; Fluck, Richard; Shardlow, Adam; Taal, Maarten
Abstract Background Multimorbidity is a growing concern for healthcare systems, with many countries experiencing demographic transition to older population profiles. Chronic kidney disease (CKD) is common but often considered in isolation. The extent and prognostic significance of its comorbidities is not well understood. This study aimed to assess the extent and prognostic significance of 11 comorbidities in people with CKD stage 3. Methods A prospective cohort of 1741 people with CKD stage 3 was recruited from primary care between August 2008 and March 2010. Participants underwent medical history, clinical assessment, blood and urine sampling. Comorbidity was defined by self-reported doctor-diagnosed condition, disease-specific medication or blood results (hemoglobin), and treatment burden as number of ongoing medications. Logistic regression was used to identify associations with greater treatment burden (taking >5 medications) and greater multimorbidity (3 or more comorbidities). Kaplan Meier plots and multivariate Cox proportional hazards models were used to investigate associations between multimorbidity and all-cause mortality. Results One thousand seven hundred forty-one people were recruited, mean age 72.9 +/−9 years. Mean baseline eGFR was 52 ml/min/1.73 m2 . Only 78/1741 (4 %) had no comorbidities, 453/1741 (26 %) had one, 508/1741 (29 %) had two and 702/1741 (40 %) had >2. Hypertension was common (88 %), 30 % had 'painful condition', 24 % anemia, 23 %, ischaemic heart disease, 17 % diabetes and 12 % thyroid disorders. Median medication use was 5 medications (interquartile range 3–8) and increased with degree of comorbidity. Greater treatment burden and multimorbidity were independently associated with age, smoking, increasing body mass index and decreasing eGFR. Treatment burden was also independently associated with lower education status. After median 3.6 years follow-up, 175/1741 (10 %) died. Greater multimorbidity was independently associated with mortality (hazard ratio 2.81 (95 % confidence intervals 1.72–4.58), p  < 0.001) for 3 or more comorbidities vs 0 or 1). Conclusions Isolated CKD was rare and multimorbidity the norm in this cohort of people with moderate CKD. Increasing multimorbidity was associated with greater medication burden and poorer survival. CKD management should include consideration of comorbidities.